Validation study of the parent attitudes about childhood vaccines (PACV) questionnaire – the Malay version / Haizlene Abd Halim - Abd Halim, Haizlene (2017)
Vaccine hesitant parents is associated with re-emergence of vaccine preventable diseases, but evidence is scarce locally. The Parent Attitudes about Childhood Vaccines (PACV) questionnaire was validated and used in the U.S.A. to identify vaccine hesitant parents. This study aimed to adapt and translate the 15-item PACV questionnaire from English into the Malay language, and to examine its validity and reliability. The study involved three phases: i) adaptation and translation, ii) face validation and iii) field testing and psychometric evaluation of the Malay version. The sample population were parents of children aged 0 – 24 months, recruited at Klinik Kesihatan Seksyen 19 Shah Alam between November 2016 – June 2017. During content validation, two items were identified as items with formative scale and excluded from exploratory factor analysis (EFA) but retained for content validity. A total of 151 parents completed the questionnaire with response rate of 93.3%. Test-retest reliability was tested in 25 respondents four weeks later and the intra-class correlation was between 0.533 – 1.000. EFA of the 13 items showed possibility of two to four factor domains, but three domains were most conceptually equivalent. One item was deleted due to poor factor loading of < 0.3. Therefore, the validated final PACV-Malay consisted of 14 items framed within four factor domains. The PACV-Malay was reliable with total Cronbach alpha of 0.74. In conclusion, the PACV-Malay is a valid and reliable tool which can be used to identify vaccine hesitant parents in Malaysia. Confirmatory factor analysis and scoring validation are recommended for future studies.